Decision Support System of Determining E-Commerce With The Topsis and Comparation With Ahp for UMKM In the Tuban Regency Area - Asfan Muqtadir; Reza Agit Alfaridzi; Amaludin Arifia (Journal of Applied Science and Technology, 2022)
E-Commerce has had a major impact on social and economic growth in society. However, E-Commerce system is not always profitable for UMKM actors themselves, there are several factors that cause UMKM quality assessments to decline from tight competitiveness. Many consumers consider buying products from the many existing E-Commerce systems. For this reason, this goal is to implement a decision support system in determining E-Commerce using the TOPSIS method with AHP method. Of course, in implementing a decision support system, it is necessary to have assessment criteria and a number of alternatives that will be used as a reference to determine E-Commerce for UMKM by calculating the TOPSIS method which will produce the final result of the value of each E-Commerce in the form of ranking. From research conducted on 38 UMKM in Tuban Regency, the results of E-Commerce Shopee are 60.5%, Tokopedia 15.8%, Blibli 10.5%, Lazada 7.9% and Bukalapak 5.3%. The data will be grouped from each alternative to find the average value based on predetermined criteria and calculated using the TOPSIS method AHP method, it can be concluded that the E-Commerce that is widely used by UMKM in the Tuban Regency area is Shopee > Tokopedia > Bukalapak > Lazada > Blibli. while with AHP resulted in the order of Tokopedia > Shopee > Bukalapak > Blibli > Lazada.